2020
DOI: 10.4194/1303-2712-v21_3_03
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Pacific Oyster, Crassostrea gigas (Bivalvia: Ostreidae), Hemocytes Under Normoxia and Short-Term Hypoxia

Abstract: Hemolymph cellular composition, morphology and functional properties of the Pacific oyster (Crassostrea gigas) hemocytes were studied. Three hemocyte types (agranulocytes, hyalinocytes and granulocytes) were described in hemolymph. The morphology of each type was characterized by light microscopy and flow cytometry. Agranular cells (agranulocytes and hyalinocytes) were the dominant type of cells in hemolymph; their number was 86.7±2.7% of total cell count. Under hypoxia the number of agranulocytes increased (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hypoxia also induced substantial increase of granulocytes and a decrease of agranulocytes and intracellular ROS production in granulocytes in the mussel M. galloprovincialis (115). However, in the oyster C. gigas, hypoxia influenced agranular and granular cells differently, with a higher decrease of ROS production in granulocytes and an increase of agranulocytes number (261,336). In the same species, O 2 deprivation resulted in a strong decrease of granulocyte mortality potentially linked with a decrease of ROS production (266).…”
Section: Abiotic Stress: Temperature Salinity Acidification Hypoxia A...mentioning
confidence: 95%
See 1 more Smart Citation
“…Hypoxia also induced substantial increase of granulocytes and a decrease of agranulocytes and intracellular ROS production in granulocytes in the mussel M. galloprovincialis (115). However, in the oyster C. gigas, hypoxia influenced agranular and granular cells differently, with a higher decrease of ROS production in granulocytes and an increase of agranulocytes number (261,336). In the same species, O 2 deprivation resulted in a strong decrease of granulocyte mortality potentially linked with a decrease of ROS production (266).…”
Section: Abiotic Stress: Temperature Salinity Acidification Hypoxia A...mentioning
confidence: 95%
“…These observations led to hypothesise that mechanisms for killing foreign particles might be different between hyalinocytes and granulocytes (204). It was also suggested that differences in ROS production between haemocyte types may be associated with the functional role and the morphological structure of each cell type (261), being granulocytes more oxygen demanding than agranular cells, because the former type possess more complicated ultrastructure with numerous mitochondria and endoplasmic reticulum (60).…”
Section: Oxidative Activitymentioning
confidence: 99%
“…Changes in total hemocyte counts, proportion of hemocyte types and phagocytosis capacity have been previously used for this purpose [31,63,64]. These hemocyte parameters vary seasonally [40], in response to infection [36,65] and susceptibility to diseases [33] and in response to different environmental conditions [27,31,32,42,66]. Thus, the knowledge of hemocyte types ofC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, light microscopy enables the comparison and classification of hemocytes types based on morphological characteristics such as cell and nucleus size and cytoplasm projections as well as staining affinities of the intracellular granules. Therefore, the combined uses of flow cytometry and light microscopy have been successfully applied to analyze the morphological characteristics of bivalve hemocytes; as reported in several studies with commercial bivalve species of mussels [37][38][39], clams [40,41] and oysters [15,17,20,22,[42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…12 Semigranulocytes have intermediate granularity. 13 Granulocytes contain the highest number of granules, and are mainly responsible for immune responses such as high phagocytic activity and reactive oxygen species (ROS) production. 14 Agranulocytes and semigranulocytes may be involved in other immune functions such as encapsulation and wound healing.…”
Section: ■ Introductionmentioning
confidence: 99%